A Primary Health Care Study on Oral Leukoplakia in State Security Riyadh KSA - Aloriny, Dr.Taufeeg Saleeh; Alqahtani, Dr.Tareq Ali (Jour Med Resh and Health Sci, 2024)
Background Oral Leukoplakia is a common pre-cancerous condition observed worldwide which often leaves physician in dilemma regarding its benign or malignant nature. Background: Oral Leukoplakia is the most common potentially malignant lesion of the oral mucosa. It is seen most frequently in middle-aged and older men, with an increasing prevalence with age. Less than one percent of men below the age of 30 years have oral leukoplakia. The etiology is multifactorial but the most common cause associated with oral leukoplakia is tobacco consumption. Biopsy is the method followed to rule out its malignant nature which is invasive and painful. Patient has to wait for the histopathology report which is usually available after a week, and sometimes even a repeat biopsy is needed. AIM: To establish the prevalence and assess the sociodemographic data along with clinical presentation of Oral Leukoplakia associated with tobacco consumption from the records of the department. Methods Here we did a detailed prospective study on morphological characteristics of 156 patients of oral leukoplakia and compared these with the biopsy outcome. Results were analysed statistically by chi square test using IBM SSPS 28 package and p values were calculated. P values less than 0.05 were taken to be significant. Results Smoking and tobacco chewing like bidi, cigratte habits, age of patient, duration, location, margins, tenderness, texture, tendency to peel easily and Induration of Oral Leukoplakia were found to be statistically significant. Conclusion Complete morphological description of Oral Leukoplakia provides significant insight to its nature during its first encounter with physician with confirmatory results provided by the biopsy. Keywords: Arecanut, Bidi, Oral Leukoplakia, Oral Precancer, Tobacco, White lesion